Características do ambiente escolar e o nível de atividade física durante o recreio de crianças das séries iniciais do ensino fundamental - Suga, Alessandra Cardozo Machado (2020)
Physical activity is a behavior that can be influenced by several characteristics of the environment. Free time at recess offers an opportunity for children to participate in physical activities by developing their motor patterns, self-confidence for the movement, and strengthening of social relationships. The facilities made available by the school can influence the way schoolchildren use recess time. The aim of this study was to analyze which characteristics of the school environment may be associated with physical activity level of children in the initial grades of elementary school during recess period. It’s a cross-sectional, observational and school-based cluster study. Participated in the study, children of 1st, 3rd and 5th grade (n=356, 51% boys) from 20 municipal schools of São José dos Pinhais-PR, close to 10 city’s Sports and Leisure Centers (two of each). The characteristics of the school’s-built environment were assessed using the “School Audit Tool”. The individual physical activity level was objectively measured using accelerometers (wGT3X-BT), classified according to the Evenson et.al., 2008 cut-off points. For descriptive characterization of the sample and school characteristics, descriptive statistics were used. To test the association between individual physical activity with the characteristics of the school environment, the multilevel linear regression was used, considering the individual characteristics (level 1) and the school environment characteristics (level 2). Analyzes were performed using SPSS version 23.0 and STATA version 13.0 and the significance level was maintained at 5%. The average duration of recess was 15 minutes and time in physical activities was 10.6 (±2.4) minutes per day. The number of functional structures on average was 12.0 (±6.0). There no associations between light and moderate physical activity with the school’s environmental variables. The activities of vigorous and moderate to vigorous intensity were associated with environmental variables: area for sport and percentage of space of available for the practice of physical activities both in the crude model and in the model adjusted for individual variables. The individual variables that were associated with vigorous physical activity were sex (female) (β- 0,48 p<0,001) and body fat percentage (β-0,04 p=0,001). For the moderate to vigorous intensity physical activity, the same individual variables showed a significant association (β-0,77 p<0,001, β-0,47 p=0,011), respectively. It is concluded that physical activities of vigorous and moderate to vigorous intensity are associated with the environmental variables, area for sport and percentage of space available for the practice of physical activities at school. These results can contribute to justify the ampliation and improvement of the spaces and structures for the practice of physical activity in schools.